DEVELOPING EFFECTIVE COMMUNICATION IN HOSPITALITY INDUSTRY : A STUDY OF CULTURAL EXPRESSIONS - Kadek Diah Purnama Dewi (Jurnal Ilmiah Hospitality Management, 2012)
This paper presents the study of cultural expressions in relation to developing effectiveÂ  communication in hospitality industry with a theoritical approach proposed by Wierzbicka (1996: 443) who states that linguistic routines are expressions which occur in more or less predictable environments and in specific social situations or in particular types of interaction. Moreover, a theory of sociography of talking proposed by Laba (2012:70-71) who argues that cross-culture communication in social interactions is influenced by and integrated into seven communication components including target, argument, language, knowledge, interlocutors, natural setting and general convention. The research method applied in this study is descriptive qualitative using ethnography approach involving social and cultural practices (Estes, 2007: 171; Bungin, 2008:23; Moleong, 2011:24-26). The discussion shows that cultural expressions is indeed an integral part of any communication, i.e. different gratitude expressions occur in social interactions influenced by the natural setting of the interlocutorsâ€™ culture and knowledge which is conceptualized in communication triangle. In Bali, this natural setting is better known as Desa (place), Kala (time) and Patra (norm) which strongly influence the communication act of the interlocutors. In order to develop more effective communication in hospitality industry, cultural expressions and the concept of communication triangle should be considered comprehensively.